2021
DOI: 10.3389/fimmu.2021.668007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis on Abnormal Methylome of Differentially Expressed Genes and Disease Pathways in the Immune Cells of RA and SLE

Abstract: We identified abnormally methylated, differentially expressed genes (DEGs) and pathogenic mechanisms in different immune cells of RA and SLE by comprehensive bioinformatics analysis. Six microarray data sets of each immune cell (CD19+ B cells, CD4+ T cells and CD14+ monocytes) were integrated to screen DEGs and differentially methylated genes by using R package “limma.” Gene ontology annotations and KEGG analysis of aberrant methylome of DEGs were done using DAVID online database. Protein-protein interaction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 85 publications
(81 reference statements)
2
24
0
Order By: Relevance
“…In addition, HERC5, RSAD2, and DDX60 are all interferon induced-genes, which play important roles in antiviral response ( 36 39 ). Consistent with our findings, recent studies revealed that the expression level of RSAD2 was markedly increased in the SLE samples compared with controls, which may act as a potential biomarker gene and therapeutic target for the treatment of SLE ( 40 , 41 ). Similarly, upregulated gene expression of DDX60 was observed in the IFN-I-positive childhood-onset SLE patients ( 42 ).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, HERC5, RSAD2, and DDX60 are all interferon induced-genes, which play important roles in antiviral response ( 36 39 ). Consistent with our findings, recent studies revealed that the expression level of RSAD2 was markedly increased in the SLE samples compared with controls, which may act as a potential biomarker gene and therapeutic target for the treatment of SLE ( 40 , 41 ). Similarly, upregulated gene expression of DDX60 was observed in the IFN-I-positive childhood-onset SLE patients ( 42 ).…”
Section: Discussionsupporting
confidence: 92%
“…Microarray data also identified 193 aberrantly methylated genes in RA monocytes. Further enrichment analysis demonstrated elevated methylation of SIRT1, SKP2, TUBA1A, IMP3, EXOSC5 and SMAD4 genes and reduced methylation of KRAS in samples from RA patients compared to healthy individuals [43]. In addition, hypomethylation of the CYP2E1 and DUSP22 promoters in RA monocytes correlates with RA activity [44].…”
Section: Role Of Dna Methylationmentioning
confidence: 97%
“…GSE93595 and GSE94550) ( 20 , 21 ) were obtained from . The gene expression matrix for the TCGA datasets was analyzed using R software v4.0.2 (limma package v3.44.3) ( 22 , 23 ) using log fold-change (FC) >0.6 or logFC <-0.6 and P<0.05 as the cut-off values, and the correlation between miR-425 and SIRT1 expression was evaluated using Pearson correlation analysis with SPSS (22.0; IBM, Corp.). GEO datasets were analyzed with GEO2R (v3.2.3) ( Table SI ) ( 24 , 25 ), and Venn diagrams were generated with VennDiagram (v1.2.20) ( 24 , 25 ).…”
Section: Methodsmentioning
confidence: 99%